2007
DOI: 10.1016/j.ab.2007.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous quantification of sialyloligosaccharides from human milk by capillary electrophoresis

Abstract: The acidic oligosaccharides of human milk are predominantly sialyloligosaccharides. Pathogens that bind sialic acid-containing glycans on their host mucosal surfaces may be inhibited by human milk sialyloligosaccharides, but testing this hypothesis requires their reliable quantification in milk. Sialyloligosaccharides have been quantified by anion exchange HPLC, reverse or normal phase HPLC, and capillary electrophoresis (CE) of fluorescent derivatives; in milk, these oligosaccharides have been analyzed by hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
2
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 30 publications
5
59
2
1
Order By: Relevance
“…Furthermore, we found that during lactation, the concentrations of sialyl oligosaccharides tended to decrease, with the exception of LSTb. Our results for the levels of sialyl HMOs were slightly different from those of Bao et al 26) but similar to those of Coppa et al 29) For instance, the concentration values for 3 0 -SL, LSTc, and LSTb in transition milk obtained in this study were a little higher and those for DSLNT a little lower than those reported by Bao et al 26) With respect to mature milk, the values we obtained are fairly well in agreement with those reported by Coppa et al 29) except that our DSLNT values were lower. This DSLNT level was higher than that described by Asakuma et al 24) for the colostrum of Japanese women.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Furthermore, we found that during lactation, the concentrations of sialyl oligosaccharides tended to decrease, with the exception of LSTb. Our results for the levels of sialyl HMOs were slightly different from those of Bao et al 26) but similar to those of Coppa et al 29) For instance, the concentration values for 3 0 -SL, LSTc, and LSTb in transition milk obtained in this study were a little higher and those for DSLNT a little lower than those reported by Bao et al 26) With respect to mature milk, the values we obtained are fairly well in agreement with those reported by Coppa et al 29) except that our DSLNT values were lower. This DSLNT level was higher than that described by Asakuma et al 24) for the colostrum of Japanese women.…”
Section: Discussioncontrasting
confidence: 56%
“…The oligosaccharides previously studied by other researchers were similar to those in the present study; their methods involved determination of peak areas in chromatograms using capillary electrophoresis, HPLC, or HPEAC-PAD of these oligosaccharides or their derivatives. 15,24,[26][27][28] Peaks 1 to 7 corresponded to 6 0 -SL, DSLNT, galacturonic acid (internal standard), LSTb, 3 0 -SL, LSTc, and LSTa respectively. The sialyl oligosaccharides isomers, 3…”
Section: Hplc Identification and Quantification Of Aa-derivatized Olimentioning
confidence: 99%
“…Several sialylated isomers have been separated with this technique however extensive isomer separation of heterogeneous mixtures still creates problems. Capillary Electrophoresis (CE) separation techniques have also been applied in the analysis of HMO (47,48). CE with laser-induced fluorescence coupled to mass spectrometry (CE-LIF-MS) is effective for derivatized HMO.…”
Section: Compound Profiling Of Hmosmentioning
confidence: 99%
“…Individual sialylated and fucosylated HMO were purchased from V-Labs (Covington, LA) and combined into a FL mix (85% [10,[13][14][15][16]. For the SL mix, we chose to mimic the total SA content of human milk [11,[17][18][19][20][21]. The 6'SL and 3'SL were added at the reported ratio to each other and the remaining total SA was provided as free SA, assuming that some lipid or protein-bound SA could be released by sialidases in the intestine [22] or by microbial fermentation [23].…”
Section: Nt and Hmo Treatmentsmentioning
confidence: 99%